Defending the Defenceless: Speciesism, Animal Liberation, and Consistency in Applied Ethics - Kemmerer, Lisa (Les ateliers de l'éthique / The Ethics Forum, 2014)
This article explores whether or not animal activists who engage in violence might legitimately be labelled “terrorists.” To this end, I examine common assumptions concerning the use of pre-emptive counter-violence in order to defend the comparatively defenceless. Through the use of casuistry, this essay compares specific hypothetical instances of killing comparatively defenceless individuals, beginning with scenarios that offer a clear general consensus, moving to more controversial cases. This indicates that contemporary violence on behalf of animal liberation, often assumed to be rash and radical, is actually quite restrained. The intent of this paper is not to make claims as to how liberationists ought to behave, but rather to highlight egregious inconsistencies in our attitudes toward violence on behalf of those who are comparatively defenceless.